2010
DOI: 10.1007/s11743-010-1224-5
|View full text |Cite
|
Sign up to set email alerts
|

Creation of Novel Green and Sustainable Gemini‐Type Cationics Containing Carbonate Linkages

Abstract: Novel gemini-type cationics containing carbonate linkages as biodegradable and chemically recyclable segments were designed and synthesized by a green process. The carbonate linkages were introduced into only the hydrophobic moiety or in both the hydrophobic and linker moieties of gemini-type cationics. They showed higher surface activities, such as a low critical micelle concentration value, a surface tension lowering, and a high adsorption efficiency, when compared to the corresponding single-type cationics.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
31
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 33 publications
5
31
0
1
Order By: Relevance
“…They appeared to be good stabilisers of polymer latex particles [30], separation agents in capillary chromatography [31], gelators of organic solvents [32], and reactants in the synthesis of silica mesophases [33]. A positive environmental impact of gemini surfactants is, apart from their low quantities used for a given application, to relate to the presence of biodegradable groups in their molecular structure such as carbon-carbon double bond [34] or carbonate linkages [35].…”
Section: Introductionmentioning
confidence: 99%
“…They appeared to be good stabilisers of polymer latex particles [30], separation agents in capillary chromatography [31], gelators of organic solvents [32], and reactants in the synthesis of silica mesophases [33]. A positive environmental impact of gemini surfactants is, apart from their low quantities used for a given application, to relate to the presence of biodegradable groups in their molecular structure such as carbon-carbon double bond [34] or carbonate linkages [35].…”
Section: Introductionmentioning
confidence: 99%
“…The biodegradability of the primary biodegradation intermediates: 1-dodecanol and trimethylene-1,3-bis( N -3-hydroxypropyl- N , N -dimethylammonium iodide) were about 70% and 10% respectively. Based on these results, one can state that the low biodegradability of studied gemini surfactant are due to the low biodegradability of the intermediate having two ammonium groups [36], [37]. Introduction of the carbonate linkage into the linker moiety between the two single-type cationics, or in both the hydrophobic and linker moieties, significantly improved the biodegrability of those surfactants.…”
Section: Resultsmentioning
confidence: 90%
“…We have also reported that carbonate linkages of gemini-type cationics are effective as biodegradable and chemically recyclable segments 9,10 .…”
mentioning
confidence: 84%